Divergence in India: income differentials at the state level, 1970-97 - Baddeley, Michelle; Cassen, Robert; McNay, Kirsty (2006)
We examine India's regional disparities in economic performance between 1970-97. Our preliminary analysis shows that, in absolute terms, initially poorer states grew at slower rates than initially wealthier ones and that there is also evidence of increasing dispersion of income levels across the states. Our econometric analysis investigates the possibility of club convergence and conditional convergence. Although we do not find evidence of the former, we can suggest some of the factors associated in the latter. Our research also indicates that the onset of economic policy reform in 1991 significantly intensified growth differentials between the states. - Reproduced.
Keywords: Income distribution - India; Income distribution